Bronchoscopic cryotherapy for advanced bronchial carcinoma. Issue 7 (July 1990) - Walsh, D A; Maiwand, M O; Nath, A R; Lockwood, P; Lloyd, M H; Saab, M
Abstract : A prospective study was carried out to assess the value of bronchoscopic cryotherapy for palliation of inoperable bronchial carcinoma with bronchial obstruction. Symptoms, lung function, and chest radiographic and bronchoscopic findings were recorded serially before and after 81 cryotherapy sessions in 33 consecutive patients. Most patients improved in terms of overall symptoms, stridor, and haemoptysis and they had an overall improvement in dyspnoea. Objective improvement in lung function was seen in 58% of patients and the changes in lung function correlated with symptoms. Bronchoscopic evidence of relief of bronchial obstruction was seen in 77% of patients and 24% showed improvement in degree of collapse on the radiograph. There were no important complications. These results compare favourably with the results in published series of patients having laser therapy. It is concluded that bronchoscopic cryotherapy is valuable for the palliation of inoperable bronchial carcinoma.